Leaf odour cues enable non‐random foraging by mammalian herbivores. (9th October 2017) - Finnerty, Patrick B.; Stutz, Rebecca S.; Price, Catherine J.; Banks, Peter B.; McArthur, Clare
Abstract: Searching for food is the first critical stage of foraging, and search efficiency is enhanced when foragers use cues from foods they seek. Yet we know little about food cues used by one major group of mammals, the herbivores, a highly interactive component of most ecosystems. How herbivores forage and what disrupts this process, both have significant ecological and evolutionary consequences beyond the animals themselves. Our aim was to investigate how free‐ranging mammalian herbivores exploit leaf odour cues to find food plants amongst a natural and complex vegetation community. Our study system comprised the native "deer equivalent" of eastern Australian forests, the swamp wallaby Wallabia bicolor, and seedlings of Eucalyptus, the foundation tree genus in these ecosystems. We quantified how foraging wallabies responded to odour cues from plants manipulated in several ways: varying the quantity of visually concealed leaves, comparing damaged vs. undamaged leaves, and whole plants vs. those with suppressed cues. The rate of discovery of leaves by wallabies increased with odour cue magnitude, yet animals were extremely sensitive to even a tiny odour source of just a few leaves. Whole seedlings were discovered faster if their leaves were damaged. Wallabies found whole seedlings and those with suppressed visual cues equally rapidly, day and night. Seedlings with very little odour were discovered mainly by day, as nocturnal foraging success was severely disrupted. This study shows how leaf odour attracts mammalian herbivores to food plants, enabling non‐random search for even tiny odour sources. As damaged leaves enhanced discovery, we suggest that the benefit of attracting natural enemies to invertebrate herbivores feeding on plants (potential "cry for help") may be offset by a cost—increased browsing by mammalian herbivores. This cost should be incorporated into multi‐trophic plant–animal studies. Finally, the breakdown in capacity to find plants at night suggests substantial but unrecognized foraging costs to herbivores when abiotic factors, such as cold temperatures or pollution, reduce or degrade plant odour cues. We predict that an increasingly polluted world will alter the foraging success of mammalian herbivores, with significant ecological ramifications given that browsing can shape ecosystems. Abstract : The authors show that mammalian herbivores use odour cues to find food plants, a mechanism for non‐random search enabling selective foraging that shapes ecosystems. The ecological implications of odour‐mediated foraging are diverse: search capability and outcomes altered by pollution, modified multi‐trophic interactions, improved foraging theories and better methods for browsing management.